2003
DOI: 10.1074/jbc.m303180200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Rap GTPases in B Lymphocytes Modulates B Cell Antigen Receptor-induced Activation of Akt but Has No Effect on MAPK Activation

Abstract: Signaling by the B cell antigen receptor (BCR) activates the Rap1 and Rap2 GTPases, putative antagonists of Ras-mediated signaling. Because Ras can activate the Raf-1/ERK pathway and the phosphatidylinositol 3-kinase (PI3K)/Akt pathway, we asked whether Rap activation limits the ability of the BCR to signal via these pathways. To do this, we blocked the activation of endogenous Rap1 and Rap2 by expressing the Rap-specific GTPase-activating protein RapGAPII. Preventing Rap activation had no effect on BCR-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 84 publications
5
39
1
Order By: Relevance
“…2) are consistent with several previous observations in B cells, where supporting evidence was mainly obtained from overexpression of activated Rap2 and the use of Rap GAPII that blocks the activation of both Rap1 and Rap2 (42,43,45). We also show that expression of constitutively active Rap2 enhances migration and, more importantly, that partial depletion of endogenous Rap2 by specific siRNA reduces migration of HSB2 T cells.…”
Section: Discussionsupporting
confidence: 80%
“…2) are consistent with several previous observations in B cells, where supporting evidence was mainly obtained from overexpression of activated Rap2 and the use of Rap GAPII that blocks the activation of both Rap1 and Rap2 (42,43,45). We also show that expression of constitutively active Rap2 enhances migration and, more importantly, that partial depletion of endogenous Rap2 by specific siRNA reduces migration of HSB2 T cells.…”
Section: Discussionsupporting
confidence: 80%
“…We observed the opposite suppressive effect on Akt activation by treatment of cells with ISO, which stimulated Rap1 in an Epac-dependent manner (Figures 3 and 4C). These findings were supported by notable studies in B-lymphocytes, in which the activation of Rap GTPases modulated the B-cell antigen receptor-mediated activation of Akt (Christian et al, 2003). A controversy in the Rap1 effect on Akt from the studies could be explained by the difference in the type of Rap1 protein expressed in one or another cell type.…”
Section: Discussionsupporting
confidence: 70%
“…Previous reports have implicated Rap1 as a positive or a negative regulator of Akt activation in various types of cells stimulated with different stimuli (Tsygankova et al, 2001;Wang et al, 2001;Lou et al, 2002;Christian et al, 2003). Although the molecular mechanisms underling these effects have not been elucidated, Rap1 has been proposed to bind PI3K through its effector-binding region, which is identical with that of Ras (Downward, 1997;Bos et al, 2001).…”
Section: Rap1 Activation By Bcr/abl and Il-3mentioning
confidence: 99%
“…Thus, depending on cell types, Rap1 may activate the MEK/Erk signaling pathway through B-Raf or may reduce its activation through its inhibitory effect on Raf-1. Similarly, recent studies have shown that Rap1 may also interact with the Ras effector PI3K and show a negative or positive effect on activation of the PI3K/Akt pathway depending on cell types and stimuli (Tsygankova et al, 2001;Wang et al, 2001;Lou et al, 2002;Christian et al, 2003). In our previous study, we found that IL-3 as well as Epo activates b1 integrin through Rap1 and induces hematopoietic cell adhesion, which agrees with recent studies showing that Rap1 plays important roles in regulation of cell adhesion through various integrins (Arai et al, 2001;Bos et al, 2001;Stork and Dillon, 2005).…”
Section: Introductionmentioning
confidence: 96%